Potential use of electrophoretic profiles in three antarctic penguin species as biological markers of contamination - Larsen, Karen Elizabeth (2012)
The effects of hydrocarbons on wild life include a variety of pathologic lesions resulting fromexternal exposition and/or ingestion.Among marine birds, penguins are particularly vulnerable to hydrocarbon pollutants from oil spills; since for this species it is difficult to detect and avoid leaked petroleum as other marine birds do. Previous works reported changes in globulin levels of electrophoretic profiles of sera from penguins dosed with fuels inAntarctica. Sera ofAdélie (Pygoscelis adeliae), Chinstrap (P. antarcticus) and Gentoo (P. papua) adult and chick penguins were analyzed by native polyacrylamide gel electrophoresis to obtain their protein profiles. The presence of immunoglobulins IgA, IgM and IgG was tested byWestern blotting.All three immunoglobulins types were present. Electrophoretic profiles of the species studied differ with those of domestic fowl (Gallus gallus) and Olrog seagull (Larus atlanticus). Characterization of immunoglobulins byWestern blot allows assessing the health status of individuals and can also be utilized as biomarkers of aquatic contamination.